The Influence of Supervisory Behavior on Employee Innovation and Creativity in Government Institutions in Koronadal City - Santillana, Edelle Lynne L.; Echalar, Lovely V. (International Journal of Research in Interdisciplinary Studies, 2025)
This study examines the influence of supervisory behavior on employee creativity and innovation in government offices in Koronadal City. The research focuses on four observable practices supervisory behavior: management support, innovation management, innovative leadership, and team innovation. These are studied despite common government challenges like limited resources, and fear of taking risks. Using a validated questionnaire adapted from Leach and Coetzee (2020), the study measured the link between supervisors’ behavior and employee creativity and innovation. The results show a moderate positive relationship, meaning supportive supervisors help create a work culture that encourages new ideas, initiative, and problem-solving. The study highlights the important role supervisors play in promoting risk-taking, sharing resources, and teamwork to keep innovation alive in public agencies. It also stresses the need to include innovation in the organizational culture through strong leadership and team efforts. Recommendations include giving supervisors more personalized support, training leaders, improving teamwork, and setting up ongoing feedback and recognition systems. These steps can help employees share new ideas, leading to better organizational performance and public service. This study adds to research on innovation in government and offers useful advice for policymakers, HR professionals, and leaders aiming to build a more innovative public sector.